2000
DOI: 10.1046/j.1471-4159.2000.0752434.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels, Metabolism, and Pharmacological Activity of Anandamide in CB1 Cannabinoid Receptor Knockout Mice

Abstract: Anandamide [arachidonylethanolamide (AEA)] appears to be an endogenous agonist of brain cannabinoid receptors (CB 1 ), yet some of the neurobehavioral effects of this compound in mice are unaffected by a selective CB 1 antagonist. We studied the levels, pharmacological actions, and degradation of AEA in transgenic mice lacking the CB 1 gene. We quantified AEA and the other endocannabinoid, 2-arachidonoyl glycerol, in six brain regions and the spinal cord by isotope-dilution liquid chromatography-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(72 citation statements)
references
References 40 publications
4
66
1
1
Order By: Relevance
“…Here, rimonabant potentiated psychostimulant-sensitization and increased anxiety whereas the genetic invalidation of the CB 1 receptor had opposite effects and reduced behavioral sensitization and failed to influence fear and anxietyrelated behaviors. Thus, our data supports the assumption of a specific rimonabantsensitive cannabinoid receptive site that is different from the 'classical' CB 1 receptor (Di Marzo, Breivogel, Tao, Bridgen, Razdan, Zimmer, Zimmer & Martin, 2000) which, under physiological conditions, seems to be involved in the inhibitory control of the acquisition but not retention of non-associative learning.…”
Section: Discussionsupporting
confidence: 85%
“…Here, rimonabant potentiated psychostimulant-sensitization and increased anxiety whereas the genetic invalidation of the CB 1 receptor had opposite effects and reduced behavioral sensitization and failed to influence fear and anxietyrelated behaviors. Thus, our data supports the assumption of a specific rimonabantsensitive cannabinoid receptive site that is different from the 'classical' CB 1 receptor (Di Marzo, Breivogel, Tao, Bridgen, Razdan, Zimmer, Zimmer & Martin, 2000) which, under physiological conditions, seems to be involved in the inhibitory control of the acquisition but not retention of non-associative learning.…”
Section: Discussionsupporting
confidence: 85%
“…Adolescence covers a developmental period of psychosocial, social and biological changes. Under normal physiological conditions in adult mice, CB1 receptors and the levels of endocannabinoid AEA and 2‐AG are abundant in the hippocampus (Di Marzo et al , 2000), a crucial structure involved in learning and memory (for review, see Zanettini et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Both pharmacological and biochemical data suggest the existence of non-CB 1 non-CB 2 cannabinoid receptors, which may be activated, at least in vitro, by physiologically relevant concentrations of AEA [5]. Di Marzo et al [5] studied levels of AEA in transgenic mice that were lacking the CB 1 gene, and suggested that non-CB 1 and non-CB 2 G protein-coupled receptors might mediate some of the neurobehavioral actions of AEA in mice. Furthermore, Zygmunt et al [6] found that AEA activates vanilloid TRPV1 receptors [4 -6].…”
mentioning
confidence: 99%